Offshore triangular TLP behaviour using dynamic morison equation - Chandrasekaran S.; Sharma A.; Srivastava S. (My University, 2025)
Tension leg platforms (TLP) are considered to be a viable concept in deep water oil explorations. Dynamic response behavior of such platforms under wave action needs more insight to optimize the platform geometry with respect to deep water conditions. In the current study, response behavior of TLPs using Dynamic Morison equation is evaluated considering nonlinearities associated with vortex shedding effects in contrast to that of conventional analysis which employs standard Morison equation. Numerical studies are carried out on two triangular TLP models under unidirectional regular waves considering the coupling between various degrees-of-freedom. The hydrodynamic forces due to the wave loading are computed using Stokes' fifth order wave theory with varying hydrodynamic coefficients Cd and Cm obtained by optimizing the force on the TLP. Results show that response behavior of triangular TLPs is sensitive to increase in water depth and hence correct estimation of hydrodynamic forces becomes very essential. It is also seen that dynamic Morison equation is capable of accounting for vortex shedding effects leading to a better modeling of fluid structure interaction which otherwise remain unaddressed.